Welcome to our free-to-use Q&A hub, where students post questions and get help from other students and tutors.

Follow the trail of responses and if you have anything to add please sign up or sign in.

You can ask your own question or look at similar Maths questions.

Applying BODMAS  rule

(2x + 13)*4 = (6x-30)*2

8x + 52 = 12x -60;

taking variable to R.H.S

112 = 4x;

x = 112/4;

x = 28


multiplying out the brackets on both sides we get

8x+52=12x-60

bringing the xs to one side, we get:

112=4x

x = 28

2(2x+13)=4(6x-30)

4x+26=24x-120

120+26=24x-4x

146=20x

x=146/20

=7.3

(2x+13):4 =(6x-30):2

means (2x+13)/4 = (6x-30)/2

implies (2x+13)*2 =(6x-30)*4

implies 4x +26 = 24x - 120

implies 120+26 = 24x-4x

implies 20x = 146

implies x = 146/20 = 7.3

therefore x = 7.3

x=11/2

It requires explanation and i dont want to solve this question you will solve it using your own mind but i can give examples and explanation

Footer Graphic